دور البرامج الدينية عبر الفضائيات الاسلامية في توعية المجتمع برنامج كيف تتعامل مع الله -نموذجا - رحومة, صباح (جامعة الوادي university of eloued, 2015)
The study aims to know the role who play it the program of how to deal with god (Allah) ؟ the second part is in community awareness from the perfect dealing with god (Allah) and the members , under the technological development and the problems that surround it. The study depended on descriptive method with using content analysis tool , and it included a number of content analysis categories which numbered 24 category , there are a verification of choosing the virtual honesty through distribution of content analysis form to a number of arbitrators specialists in the field of media studies and social study. To achieve the goal through study , which it included all episodes of how to deal with god (Allah) ? the second part using comprehensive inventory method so that the sample consisted of 26 episodes out of 29 , this is because we took the first three episodes which is containing his story with a question , how to deal with god (Allah) ? and the twenty eighth episode recorded , ( video ) The last episode which included a selection of the best episodes that offered . The study concluded that the program of how to deal with god (Allah) ? the second part is doing the job of counseling and guidance , and this is a program that how to deal with god (Allah) ؟ the second part It has an important role in educating the community
مذكرة
Keywords: Role , Religious programs , Islamic satellite channels , Awareness , Community